Nominal anchors in EU accession countries: Recent experiences - Michael Frömmel; Franziska Schobert (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
We investigate official and implicit nominal anchors for six Central and Eastern European countries during 1994 to 2002. Most of these countries have moved from fixed to more flexible regimes and adopted a form of inflation targeting. Achieving their new official targets has had mixed success. Furthermore, we find some evidence for implicit exchange rate targeting. It seems to be most pronounced for Slovenia, whereas the results for Hungary and Poland match the officially announced regimes. Consequently, moving officially to more flexible arrangements does not always lead to a de facto move.
Keywords: F31; 330; Transition economies; exchange rate regimes; nominal anchors; fear of floating; exchange rate volatility; GARCH; Wechselkurssystem; Währungspolitik; Inflation Targeting; EU-Erweiterung; Schätzung; Osteuropa